Competencias Docentes En El Uso Y Aplicación De Las Tic En San Juan Girón (Colombia) - Glenn Elmer Hernández Camelo; Juan Manuel Trujillo Torres (European Scientific Journal, ESJ, 2016)
The study is part of a doctoral research on a model of teacher training to address approach the teaching process by educational technology, which aims to establish the percentage of teachers in the municipality of San Juan Giron (Colombia) with technology skills information and communication and how many of them apply them in the classroom. A questionnaire and an interview with principals, coordinators, teachers and students who are part of the public education system was applied. Data on correlation nonparametric tests, frequency tables and histograms and two-dimensional descriptive statistics in order to quantify the degree of association between variables analyzes were performed. The results relate to the percentages of skills in information and communication technologies which has the population studied, showing low rates of application of the same in the education sector and in the classroom. Among the most notable contributions it was found that the educational community is aware of the existence of technological tools but is not trained in the management of computing resources or the development of educational resources to support teaching because of the lack of effective plans educational and training models of teacher training, which has not allowed the pedagogical use of ICT in educational institutions. It is necessary to develop and implement a model of teacher training in ICT to respond to the educational reality of the schools in San Juan Giron.